2022
DOI: 10.3389/fpubh.2022.697386
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Barriers to Prenatal Physical Activity and Exercise Among South African Pregnant Women: A Cross-Sectional, Mixed-Method Analysis

Abstract: BackgroundThe barriers to prenatal physical activity and exercise have been widely reported in the literature, highlighting context-specific challenges. However, generally, research on prenatal physical activity and exercise among pregnant women in South Africa is rare; and particularly concerning the barriers to their prenatal physical activity practice. This study assessed the barriers to physical activity participation among pregnant women in the Eastern Cape, South Africa.MethodsThis was a sequential expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Of note is a prospective study from Spain that found that nearly half of 1,175 pregnant women engaged in su cient PA before pregnancy but did not maintain their PA level during pregnancy [9]. This may be attributed to physical discomfort during pregnancy, in particular nausea and vomiting [40], which is consistent with our ndings, in addition to low back pain, fatigue, fear of injury, and uncertainty about the safety of exercising during pregnancy [41].…”
Section: Discussionsupporting
confidence: 85%
“…Of note is a prospective study from Spain that found that nearly half of 1,175 pregnant women engaged in su cient PA before pregnancy but did not maintain their PA level during pregnancy [9]. This may be attributed to physical discomfort during pregnancy, in particular nausea and vomiting [40], which is consistent with our ndings, in addition to low back pain, fatigue, fear of injury, and uncertainty about the safety of exercising during pregnancy [41].…”
Section: Discussionsupporting
confidence: 85%
“…However, in this study, the lack of exercise programmes and affordable, safe environments for some participants was said to have resulted in a decrease in physical activity. Similarly, in South Africa, the results of Okafor and Goon [24] showed that the lack of physical activity facilities, including recreational facilities, and the fear of being mugged by some criminals on the street had a negative impact on the physical activity of pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…The initiation of an exercise program during pregnancy may present distinct problems for pregnant women who were sedentary or had low levels of physical activity before to conception. 10 Pregnant women who have been sedentary or previously inactive are advised to initiate their exercise routine with low-intensity activities, such as walking or prenatal yoga, and subsequently augment the time and intensity of these activities as they are able to endure. 24 In order to facilitate appropriate adaptation and mitigate the likelihood of musculoskeletal injuries, it may be imperative to implement a more gradual progression and extend duration of warm-up and cool-down periods.…”
Section: Sedentary Women and Those With Low Physical Activity Levelsmentioning
confidence: 99%
“…9 Furthermore, pregnant women may face a range of obstacles when it comes to engaging in physical activity, such as insufficient energy levels, limited time availability, inadequate access to appropriate facilities, or apprehensions regarding the potential effects on the pregnancy. 10 In addressing these issues and promoting the safe and successful engagement of pregnant mothers in physical activity, healthcare providers assume a pivotal role. 11 Given the considerable potential advantages and the necessity to traverse the intricate array of considerations, it is imperative to cultivate a full comprehension of the role of physical activity during pregnancy.…”
Section: Introductionmentioning
confidence: 99%